Second intravenous immunoglobulin dose in patients with Guillain-Barré syndrome with poor prognosis (SID-GBS): a double-blind, randomised, placebo-controlled trial. Issue 4 (April 2021) - Walgaard, Christa; Jacobs, Bart C; Lingsma, Hester F; Steyerberg, Ewout W; van den Berg, Bianca; Doets, Alexandra Y; Leonhard, Sonja E; Verboon, Christine; Huizinga, Ruth; Drenthen, Judith; Arends, Samuel; Budde, Ilona Kleine; et al.
Summary: Background: Treatment with one standard dose (2 g/kg) of intravenous immunoglobulin is insufficient in a proportion of patients with severe Guillain-Barré syndrome. Worldwide, around 25% of patients severely affected with the syndrome are given a second intravenous immunoglobulin dose (SID), although it has not been proven effective. We aimed to investigate whether a SID is effective in patients with Guillain-Barré syndrome with a predicted poor outcome. Methods: In this randomised, double-blind, placebo-controlled trial (SID-GBS), we included patients (≥12 years) with Guillain-Barré syndrome admitted to one of 59 participating hospitals in the Netherlands. Patients were included on the first day of standard intravenous immunoglobulin treatment (2 g/kg over 5 days). Only patients with a poor prognosis (score of ≥6) according to the modified Erasmus Guillain-Barré syndrome Outcome Score were randomly assigned, via block randomisation stratified by centre, to SID (2 g/kg over 5 days) or to placebo, 7–9 days after inclusion. Patients, outcome adjudicators, monitors, and the steering committee were masked to treatment allocation. The primary outcome measure was the Guillain-Barré syndrome disability score 4 weeks after inclusion. All patients in whom allocated trial medication was started were included in the modified intention-to-treat analysis. This study is registered with the Netherlands Trial Register, NTR 2224/NL2107. Findings: Between Feb 16, 2010, and June 5, 2018, 327 of 339 patients assessed for eligibility were included. 112 had a poor prognosis. Of those, 93 patients with a poor prognosis were included in the modified intention-to-treat analysis: 49 (53%) received SID and 44 (47%) received placebo. The adjusted common odds ratio for improvement on the Guillain-Barré syndrome disability score at 4 weeks was 1·4 (95% CI 0·6–3·3; p=0·45). Patients given SID had more serious adverse events (35% vs 16% in the first 30 days), including thromboembolic events, than those in the placebo group. Four patients died in the intervention group (13–24 weeks after randomisation). Interpretation: Our study does not provide evidence that patients with Guillain-Barré syndrome with a poor prognosis benefit from a second intravenous immunoglobulin course; moreover, it entails a risk of serious adverse events. Therefore, a second intravenous immunoglobulin course should not be considered for treatment of Guillain-Barre syndrome because of a poor prognosis. The results indicate the need for treatment trials with other immune modulators in patients severely affected by Guillain-Barré syndrome. Funding: Prinses Beatrix Spierfonds and Sanquin Plasma Products.